Multi-Criteria Analysis to Prioritize Energy Sources for Ambience in Poultry Production - DC Collatto; RB Mansilha; LD Chiwiacowsky; DP Lacerda (Brazilian Journal of Poultry Science)
ABSTRACT This paper intends to outline a model of multi-criteria analysis to pinpoint the most suitable energy source for heating aviaries in poultry broiler production from the point of view of the farmer and under environmental logic. Therefore, the identification of criteria was enabled through an exploratory study in three poultry broiler production units located in the mountain region of Rio Grande do Sul. In order to identify the energy source, the Analytic Hierarchy Process was applied. The criteria determined and validated in the research contemplated the cost of energy source, leadtime, investment in equipment, energy efficiency, quality of life and environmental impacts. The result of applying the method revealed firewood as the most appropriate energy for heating. The decision support model developed could be replicated in order to strengthen the criteria and energy alternatives presented, besides identifying new criteria and alternatives that were not considered in this study.